SENSITIVITY OF Microsporum canis ISOLATED FROM DOGS TOWARDS ANTIFUNGALS - I Sakan, Gerson Yohanes; Indarjulianto, Soedarmanto; Nururrozi, Alfarisa; Yanuartono, Yanuartono; Raharjo, Slamet (Universitas Syiah Kuala, 2020)
The dermatophytosis treatment in dogs can fail due to dermatophyte resistance to antifungals. The purpose of this study is to determine the antifungal sensitivity of dermatophyte Microsporum canis (M. canis) isolated from dogs with dermatophyte. A total of 17 M. canis dog isolateswere tested for sensitivity to 25 g fluconazole, 25 g griseofulvin, 15 g ketoconazole and 30 g terbinafine, using the disc diffusion method.The M. canis isolates were cultured on Sabouraud's Dextrose Agar media, placed an antifungal disc, and then incubated at 28 C for 7 days. Thediameter of inhibition zone was measured, then compared with the standard, to determine whether they were sensitive, intermediate or resistant.The results of this study indicate that 16 isolates were sensitive to fluconazole; 17 isolates were sensitive to griseofulvin, ketoconazole andterbinafine; and one isolate was intermediate to fluconazole. Based on these results, it is concluded that all 17 (100%) isolates are sensitive to theantifungals griseofulvin, ketoconazole, terbinafine, and 16 (94%) isolates are sensitive to fluconazole. Thus, the four antifungals can be selectedto treat dermatophytes in dogs.